The latent stage of Toxoplasma gondii is targeted by the immune response and host protective - Shallberg, Lindsey A; Eberhard, Julia N; Winn, Aaron; Chandrasekaran, Sambamurthy; Giuliano, Christopher J; Merritt, Emily F; Willis, Elinor; Christian, David A; Aldridge, Daniel L; Bunkofske, Molly; Jacquet, Maxime; Dzierszinski, Florence; et al. (bioRxiv, 2024)
Latency is a microbial strategy for persistence. For Toxoplasma gondii the ability of the bradyzoite stage to form long-lived cysts is critical for transmission, while their presence in neurons is considered important for immune evasion. Development of a mathematical model highlighted that immune pressure on bradyzoites should contribute to dynamics of cyst formation and reactivation. Experimental data demonstrated that a cyst-derived antigen was recognized by CD8+ T cells and that IFN-γ signaling in neurons contributes to cyst control. In addition, modeling and the use of a parasite strain unable to form bradyzoites revealed that this stage was not required for long-term persistence, but the absence of cyst formation resulted in increased tachyzoite replication in the CNS with associated tissue damage and mortality. Thus, the latent form of T. gondii is under immune pressure, mitigates infection-induced damage, and promotes survival of host and parasite.Competing Interest StatementThe authors have declared no competing interest.